Theatre in Times of Crisis : 20 Scenes for the Stage in Troubled Times /: 20 Scenes for the Stage in Troubled Times. (2020) - Bond, Edward; Adebayo, Mojisola; Bhuchar, Sudha; Bhatti, Gurpreet Kaur; Cooper, Zöe; Ya-Chu Cowhig, Frances; Crouch, Tim; Ellams, Inua; Graham, James; Gupta, Tanika; Khalil, Hannah; Malcolm, Morgan Lloyd; et al.
No abstract available